Exploring the Role of Animated Video Design in English Language Learning Through Student Experiences - Rohmatul Azizah; M. Hanafi; Mohammad Luqman (Raja Zulkarnain Education Foundation, 2025)
This qualitative study investigates the role of animated video design in English language learning by examining student experiences in junior high school classrooms. As educational technology continues to evolve, animated videos have become an increasingly popular tool to facilitate language acquisition. This research explores how specific design elements such as visuals, narrative flow, character development, and audio features influence students’ engagement, motivation, and cognitive processing. Data were collected through semi-structured interviews and classroom observations involving junior high school students. Findings indicate that well-crafted animated videos can create an immersive and stimulating learning environment that supports comprehension and retention of English language concepts. Additionally, students emphasized the significance of relatable characters and clear storylines in maintaining their interest and enhancing understanding. The study provides practical insights for educators and content creators aiming to optimize animated video design for effective language learning.